On the maximum energy of shock-accelerated cosmic rays at ultra-relativistic shocks - Reville, B; Bell, A (Blackwell Publishing Ltd, 2014)
The maximum energy to which cosmic rays can be accelerated at weakly magnetised ultrarelativistic shocks is investigated.We demonstrate that for such shocks, in which the scattering of energetic particles is mediated exclusively by ion skin-depth scale structures, as might be expected for a Weibel-mediated shock, there is an intrinsic limit on the maximum energy to which particles can be accelerated. This maximum energy is determined from the requirement that particles must be isotropized in the downstream plasma frame before the mean field transports them far downstream, and falls considerably short of what is required to produce ultra-high-energy cosmic rays. To circumvent this limit, a highly disorganized field is required on larger scales. The growth of cosmic ray-induced instabilities on wavelengths much longer than the ion-plasma skin depth, both upstream and downstream of the shock, is considered. While these instabilities may play an important role in magnetic field amplification at relativistic shocks, on scales comparable to the gyroradius of the most energetic particles, the calculated growth rates have insufficient time to modify the scattering. Since strong modification is a necessary condition for particles in the downstream region to re-cross the shock, in the absence of an alternative scattering mechanism, these results imply that acceleration to higher energies is ruled out. If eakly magnetized ultra-relativistic shocks are disfavoured as highenergy particle accelerators in general, the search for potential sources of ultra-high-energy cosmic rays can be narrowed. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.